518 DUAL ANTIPLATELET THERAPY DE-ESCALATION MODALITIES IN ACUTE CORONARY SYNDROME PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION. (15th December 2022) - Greco, Antonio; Laudani, Claudio; Occhipinti, Giovanni; Scalia, Lorenzo; Agnello, Federica; Legnazzi, Marco; Mauro, Maria Sara; Rochira, Carla; Buccheri, Sergio; Mehran, Roxana; James, Stefan; Angiolillo, Dominick; et al.
Abstract: Background: Dual antiplatelet therapy (DAPT) is usually recommended for 12 months after an acute coronary syndrome (ACS). A major drawback of DAPT is represented by an increased risk of bleeding events, which have a detrimental impact on short and long-term prognosis. To minimize this risk, bleeding modulation strategies can be adopted, including de-escalating to a lower intensity DAPT regimen (i.e., halving the dose of a potent P2Y12 -inhibitor or switching to clopidogrel). Whether either DAPT de-escalation modality is associated with improved clinical outcomes is unknown. Purpose: To investigate the role of DAPT de-escalation in ACS patients undergoing PCI as compared to standard DAPT, and to indirectly compare two DAPT de-escalation modalities (i.e., by halving P2Y12 -inhibitor dose or switching from a potent P2Y12 -inhibitor to clopidogrel) by means of a network meta-analysis using standard DAPT as a common comparator. Methods: MEDLINE, Cochrane and Web Of Science were searched for randomised trials of DAPT de-escalation strategies in ACS patients undergoing PCI. The primary outcome was all-cause death, while secondary outcomes included net adverse cardiovascular events (NACE), major adverse cardiovascular events (MACE), and their individual components. A network meta-analysis was performed to indirectly compare different DAPT de-escalation modalities (i.e., halving the dose of a potent P2Y12 -inhibitor or switching to clopidogrel). Results: A total of 12, 813 from ten studies were included for the purposes of this analysis. In the pairwise meta-analysis, there were no significant differences between DAPT de-escalation and standard DAPT in terms of all-cause death (risk ratio [RR] 0.85, 95% confidence interval [CI] 0.62 to 1.18), MACE (RR 0.83, 95% CI 0.69 to 1.00), cardiovascular death (RR 0.78, 95% CI 0.56 to 1.07), myocardial infarction (RR 0.80, 95% CI 0.58 to 1.09), stent thrombosis (RR 0.74, 95% CI 0.37 to 1.47) and major bleeding (RR 0.88, 95% CI 0.66 to 1.17). Compared to standard DAPT, de-escalation was associated with a lower risk of NACE (RR 0.76, 95% CI 0.68 to 0.85), clinically relevant bleeding (RR 0.65, 95% CI 0.51 to 0.84) and minor bleeding (RR 0.63, 95% CI 0.54 to 0.74). In the indirect comparison, there were no significant differences between de-escalation by switching to clopidogrel and de-escalation by halving the P2Y12 -inhibitor dose in terms of all-cause death (RR 1.24, 95% CI 0.51 to 2.99), NACE (RR 1.10, 95% CI 0.81 to 1.48), MACE (RR 1.10, 95% CI 0.59 to 2.06) and clinically relevant bleeding (RR 1.16, 95% CI 0.60 to 2.21). Conclusions: DAPT de-escalation was associated with a lower risk of NACE, clinically relevant bleeding and minor bleeding compared to standard DAPT in ACS patients undergoing PCI. There is no consensus on the optimal DAPT de-escalation modality and further research in this field is warranted since halving the dose of a potent P2Y12 -inhibitor and switching to clopidogrel resulted to be similar in terms of net clinical benefit and both ischemic and bleeding events, therefore representing two viable options in ACS patients undergoing PCI.